2017
DOI: 10.12973/ijem.3.1.25
|View full text |Cite
|
Sign up to set email alerts
|

Children’s Play and Physical Activity in Traditional and Forest (Natural) Playgrounds

Abstract: Early childhood is a crucial period for the physical and cognitive development of children. A child's exposure to nature is proven to be beneficial in this period of human life. The aim of the present research was to investigate children's play and physical activity on a traditional playground and on a forest (natural) playground. Twenty-five observations took place on the traditional playground, and twenty-five observations were recorded on the forest playground. Twenty-five participating preschool children w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 10 publications
(6 reference statements)
0
16
0
Order By: Relevance
“…There were several methodological concerns amongst the included studies. The main concerns were: sample size not being described in detail (only eight studies Systematic review of nature play and child health described their sample [73][74][75][76][77][78][79][80]; the lack of sample size justification (only three studies did this [73,74,81]; lack of reliability and validity of outcome measures [ten studies reported on reliability [73-76, 78, 79, 81-84] and seven reported on validity [73-76, 81, 82, 84]; and finally the lack of reporting dropouts, with only six studies reporting dropout rates [5,74,75,81,83,84].…”
Section: Risk Of Bias Within Studiesmentioning
confidence: 99%
See 4 more Smart Citations
“…There were several methodological concerns amongst the included studies. The main concerns were: sample size not being described in detail (only eight studies Systematic review of nature play and child health described their sample [73][74][75][76][77][78][79][80]; the lack of sample size justification (only three studies did this [73,74,81]; lack of reliability and validity of outcome measures [ten studies reported on reliability [73-76, 78, 79, 81-84] and seven reported on validity [73-76, 81, 82, 84]; and finally the lack of reporting dropouts, with only six studies reporting dropout rates [5,74,75,81,83,84].…”
Section: Risk Of Bias Within Studiesmentioning
confidence: 99%
“…The study characteristics from the 16 included studies are displayed in Table 2. A range of study designs were identified, as were the geographical study locations, which included Norway [76,81,82], Slovenia [5], Australia [20,77], United Kingdom [77], Scotland [85], Canada [75], United States of America [73,78,83,84] and Germany. The studies were conducted from 2001 onwards to the most recent three studies published in 2018 [74,77,84] which may indicate the relatively recent interest in nature play.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations